Embedding internationalization in European higher education institution´s strategies: easier said than done? - González-Bonilla, Alejandra; Blanco Carrasco, Marta; Castaño Collado, Gloria; Urquía Grande, Elena (Papeles de Europa, 2021)
This paper portrays the findings of a joint mixed-method exploratory Survey (JIPS) carried out among 85 European Higher Education Institutions (HEIs) in 18 countries. Its aims are to identify common problematic issues in European internationalization Higher Education strategic designs and practices, through exploring the perceptions of international administrative and academic actors. The study reveals a contradiction between internationalization as an institutional vowed priority and what HEIs do in the practice. Three main weaknesses are detected: lack of planning, scarce internal quality review practices, and deficient bi-directional internal communication and participation of staff in decision-making processes.